Standard methods for the examination of water and wastewater (American Public Health Association, 1998)
The twentieth edition has maintainnedcthe trend of the Nine teenth edition in continued renewal of part 1000. Significant revision has occurred in the sections on data quality (1030) sampling (1060) and reagent water (1080),...